Pemberdayaan Masyarakat Melalui Pemanfaatan Limbah Jerami dan Sekam Padi Menjadi Superkarbon di Kecamatan Moyudan, Sleman - Fatwa Tentama; Surahma Asti Mulasari; Desta Risky Kusuma (Universitas Mathla'ul Anwar Banten, 2017)
COMMUNITY EMPOWER THROUGH UTILIZATION OF STRAW WASTE AND RICE HUSK BECOME SUPERCARBON IN MOYUDAN, SLEMAN. Karanganjir, Sejati Dukuh and Setran are three hamlets in the village Sumberarum. The livelihoods of the majority of the population worked as farmers. Each season rice harvest paddy lands in Karanganjir, Sejati Dukuh and Setran will produce abundant rice. Results of the rice harvest in the form of straw and rice husks were also plentiful. Rural farming communities Sumberarum have not been able to utilize the waste straw and rice husks are plentiful. This is due to the lack of awareness, knowledge, and skills for the use of waste straw and rice husks. Pollution of the environment requires a solution that is by utilizing the waste straw and rice husks into supercarbon as kerosene and gas for household and economic value. The program will work closely with youth organizations and farmers’ groups in Karanganjir, Sejati Dukuh and Setran, Co-operative of Sumberarum village, Co-operative of Universitas Ahmad Dahlan (UAD), and Department of Industry Trade and Cooperatives of Sleman. This program is conducted by lecturers and UAD students of Community Service Program (KKN) divided into five major themes: 1) Entrepreneurship; 2) Making supercarbon from agricultural waste; 3) Utilization supercarbon as an alternative fuel; 4) Motivating supercarbon entrepreneurship; 5) The establishment and development of business units supercarbon.